Indirect industrial effects from space investments. (November 2016) - Eerme, Tõnis
Abstract: Many impact assessments have been carried out to evaluate the economic and social effects of public investments in space. This paper focuses on ex post analyses of indirect industrial (intra-firm) effects, a sub-type of the impact assessments. A number of existing country-wide analyses report the ratio of the indirect industrial effects deriving from space-related contracts to the value of the space-related contracts placed with companies by governmental agencies (in Europe, mostly by the European Space Agency). This ratio is a widely accepted measure of the economic impact of the space contracts. The aim of this paper is to assess the usefulness of the ratio, a spin-off multiplier, for international benchmarking of the efficiency of space investments. The paper is the first attempt to provide an in-depth analysis of the methodological foundations of different country-wide studies on the spin-off multiplier performed in Europe. The country-wide studies have formulated different metrics and relied on different approaches to gathering quantitative data. The current paper discusses data quality issues that may result in a biased estimate of the spin-off multiplier. Data gathering techniques used in the studies tend to result in overestimated economic benefits. Even though the values of the spin-off multipliers are high in countries like Norway or Denmark, the confidence interval of the estimates is wide. The paper discusses time considerations to be taken into account for a standardized ratio as there is a time lag of several years until research and development becomes operative. Despite several methodological limitations, measuring the indirect industrial effects is a valuable tool for governments, especially for smaller ESA member states, as such studies can be implemented at low cost and provide information on spillovers from space programmes.